(untitled) (Clinics, 2011)
INTRODUCTION: In obsessive-compulsive disorder, early treatment discontinuation can hamper the effectiveness of first-line treatments. OBJECTIVE: This study aimed to investigate the clinical correlates of early treatment discontinuation among obsessive-compulsive disorder patients. METHODS: A group of patients who stopped taking selective serotonin reuptake inhibitors (SSRIs) or stopped participating in cognitive behavioral therapy before completion of the first twelve weeks (total n = 41; n = 16 for cognitive behavioral therapy and n = 25 for SSRIs) were compared with a paired sample of compliant patients (n = 41). Demographic and clinical characteristics were obtained at baseline using structured clinical interviews. Chisquare and Mann-Whitney tests were used when indicated. Variables presenting a p value